1991
DOI: 10.1029/91jd01358
|View full text |Cite
|
Sign up to set email alerts
|

Air mass origins and troposphere‐to‐stratosphere exchange associated with mid‐latitude cyclogenesis and tropopause folding inferred from 7Be measurements

Abstract: The 1984 extratropical mission of NASA's Stratosphere‐Troposphere Exchange Project (STEP) studied cross‐jet transports in regions of cyclogenesis and tropopause folding. Correlations of 7Be, ozone, water vapor, and potential vorticity measured on a NASA U‐2 research aircraft flying in high shear regions above the jet core are indicative of mixing between the cyclonic and the anticyclonic sides of the jet and are consistent with the hypothesis that small‐scale entrainments of upper tropospheric air into the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Danielsen, 1968;Shapiro, 1980;Kritz et al, 1991). In addition, convection has been identified injecting boundary layer air directly into the lowermost stratosphere within several hours (Poulida et al, 1996;Fischer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Danielsen, 1968;Shapiro, 1980;Kritz et al, 1991). In addition, convection has been identified injecting boundary layer air directly into the lowermost stratosphere within several hours (Poulida et al, 1996;Fischer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of 7 Be in surface air depend on cosmic ray intensity, highly variable stratosphere-troposphere exchange, downward transport of the aerosols in the troposphere resulting from the mixing of air through the depth of the troposphere, assumed to vary between 10 and 30 days depending on latitude, and wet and dry deposition of the carrier aerosols. [15][16][17][18][19][20][21] Consequently, the variability of 7 Be at a given spatial location is a sensitive indicator of intrusions of stratospheric air into the troposphere, over a base tropospheric turn over time. Thus, quantifying the 7 Be content in fine aerosols can give a measure of the transport of this fine aerosol material from the upper troposphere/lower stratosphere to the surface where it is sampled.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, quantifying the 7 Be content in fine aerosols can give a measure of the transport of this fine aerosol material from the upper troposphere/lower stratosphere to the surface where it is sampled. Past work has suggested that this might be a useful way to determine stratospheric intrusions into the lower atmosphere and also to estimate the maximum extent to which stratospheric O 3 is affecting tropospheric sites during tropopause folding events, 9,[15][16][17][18][19][20][21]28,29 generally associated with intense storm events and frontal movements in the midlatitude northern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…In spring time a rapid removal from lower polar troposphere to the troposphere at the northern hemisphere is well known [28] and possibly due to folding of the troposphere during April and May at the mid-latitude (30-50) enhances the removal of the stratospheric 7 Be into the troposphere [29,30]. It is worth mentioning that the 7 Be deposition rate in March 2011 was considerably lower in spite of a massive dust event suggest limited dry deposition of 7 Be in the study area (Fig.…”
Section: Resultsmentioning
confidence: 99%